Small extracellular vesicles induce resistance to anti-GD2 immunotherapy unveiling tipifarnib as an adjunct to neuroblastoma immunotherapy. Issue 4 (28th April 2022) - Liu, Xiaoming; Wills, Carson A; Chen, Longgui; Zhang, Jiawen; Zhao, Yuanjun; Zhou, Mi; Sundstrom, Jeffrey M; Schell, Todd; Spiegelman, Vladimir S; Young, Megan M; Wang, Hong-Gang
Abstract : Background: Anti-GD2 monoclonal antibody immunotherapy has significantly improved the overall survival rate for high-risk neuroblastoma patients. However, 40% of patients fail to respond or develop resistance to treatment, and the molecular mechanisms by which this occurs remain poorly understood. Tumor-derived small extracellular vesicles (sEVs) have emerged as critical regulators in modulating the response to immunotherapy. In this study, we investigated the role of neuroblastoma-derived sEVs in promoting resistance to the anti-GD2 monoclonal antibody dinutuximab. Moreover, to determine whether pharmacologic inhibition of sEV secretion sensitizes tumors to dinutuximab treatment, we combined dinutuximab with tipifarnib, a farnesyltransferase inhibitor that inhibits sEV secretion. Methods: We investigated the role of neuroblastoma-derived sEVs in modulating the response to dinutuximab by utilizing the syngeneic 9464D-GD2 mouse model. The effect of neuroblastoma-derived sEVs in modulating the tumor microenvironment (TME) and host immune system were evaluated by RNA-sequencing and flow cytometry. Importantly, we used this mouse model to investigate the efficacy of tipifarnib in sensitizing neuroblastoma tumors to dinutuximab. The effect of tipifarnib on both the TME and host immune system were assessed by flow cytometry. Results: We demonstrated that neuroblastoma-derived sEVs significantly attenuated the efficacy of dinutuximab in vivo and modulated tumor immune cell infiltration upon dinutuximab treatment to create an immunosuppressive TME that contains more tumor-associated macrophages and fewer tumor-infiltrating NK cells. In addition, we demonstrated that neuroblastoma-derived sEVs suppress splenic NK cell maturation in vivo and dinutuximab-induced NK cell-mediated antibody-dependent cellular cytotoxicity in vitro . Importantly, tipifarnib drastically enhanced the efficacy of dinutuximab-mediated inhibition of tumor growth and prevented the immunosuppressive effects of neuroblastoma-derived sEVs in vivo . Conclusions: These preclinical findings uncover a novel mechanism by which neuroblastoma-derived sEVs modulate the immune system to promote resistance to dinutuximab and suggest that tipifarnib-mediated inhibition of sEV secretion may serve as a viable treatment strategy to enhance the antitumor efficacy of anti-GD2 immunotherapy in high-risk neuroblastoma patients.